Association of Factor V Leiden Mutation with Delayed Graft Function, Acute Rejection Episodes and Long-term Graft Dysfunction in Kidney Transplant Recipients - Hocher, Berthold; Slowinski, Torsten; Hauser, Ingeborg; Vetter, Birgit; Fritsche, Lutz; Bachert, Daniela; Kulozik, Andreas; Neumayer, Hans-H. (Thrombosis and Haemostasis, 2002)
We analysed whether the factor V Leiden mutation – the most common hereditary predisposing factor for venous thrombosis – is associated with early and long-term graft dysfunction after kidney transplantation in 394 Caucasian kidney transplant recipients. The presence of factor V Leiden mutation was identified by allele specific PCR. The prevalence of the factor V Leiden mutation was compared to 32216 unselected neonates. The prevalence of the factor V Leiden mutation (GA genotype) was similar in 394 kidney transplant recipients and 32216 neonates. The frequency of known factors predicting long-term graft function were similar in patients with the GA genotype and with the normal factor V gene (GG genotype). The GA genotype was associated with the occurrence of no primary graft function (risk: 2.87; 95% confidence interval: 1.01-8.26; p < 0.05), the number of dialysis after transplantation in patients with no primary graft function until graft function (7.5 ± 2.06 dialysis in GA patients; 4.2 ± 0.36 dialyses in GG patients; p < 0.05), and the risk for at least one acute rejection episode (risk: 3.83; 95% confidence interval: 1.38-10.59; p < 0.02). The slope of 1/creatinine per year was significantly lower in patients with the GA genotype (GA patients: – 0.0204 ± 0.008 dl/mg per year; GG patients: 0.0104 ± 0.004 dl/mg per year; p < 0.02). The annual enhancement of the daily protein excretion rate was elevated in patients with the GA genotype (GA patients: 38.5 ± 16.6 mg/24 h per year; GG patients: 4.9 ± 4.4 mg/24 h per year; p < 0.02). Our study showed that the factor V Leiden mutation is associated with the occurrence of delayed graft function, acute rejection episodes and chronic graft dysfunction after kidney transplantation.
Keywords: Factor V Leiden mutation; kidney transplantation